2023
DOI: 10.1017/s0007114523001812
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in iron status during military training: a prospective cohort study of longitudinal changes and associations with endurance performance and musculoskeletal outcomes

Thomas J. O’Leary,
Sarah Jackson,
Rachel M. Izard
et al.

Abstract: This study investigated sex differences in iron status, and associations between iron status and endurance and musculoskeletal outcomes, in military training. 2,277 British Army trainees (581 women) participated. Iron markers and endurance performance (2.4 km run) were measured at the start (week 1) and end (week 13) of training. Whole-body areal body mineral density (aBMD) and markers of bone metabolism were measured at week 1. Injuries during training were recorded. Training decreased haemoglobin in men and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
2
0
1
Order By: Relevance
“…In our conscripts, hemoglobin levels did not change during BMT in the S-C, but there was a small (3.7%) statistically significant increase in the A-C. Contrary to our data, other research groups [63][64][65] observed a decrease in hemoglobin levels in male soldiers during BMT, lasting from 9 weeks to 4 months. The discrepancy between our findings and those of the previous studies may be due to many factors, such as the duration of training, the proportions of training loads with different goals, nutrient intake, and the physical performance of soldiers before the start of military training.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In our conscripts, hemoglobin levels did not change during BMT in the S-C, but there was a small (3.7%) statistically significant increase in the A-C. Contrary to our data, other research groups [63][64][65] observed a decrease in hemoglobin levels in male soldiers during BMT, lasting from 9 weeks to 4 months. The discrepancy between our findings and those of the previous studies may be due to many factors, such as the duration of training, the proportions of training loads with different goals, nutrient intake, and the physical performance of soldiers before the start of military training.…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, a significant decrease in ferritin levels observed during BMT in both S-C (14.6%) and A-C (39.4%) is in good agreement with previous data [63][64][65][66]. With a background of relatively stable hemoglobin concentrations, a decrease in ferritin levels did not prevent the improvement in aerobic endurance during BMT in our conscripts.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation